Synthesis, crystal structure and desulfurization properties of zig-zag 1D coordination polymer of copper(II) containing 4-methoxybenzoic acid ligand. (2nd November 2018) - Tella, Adedibu C.; Owalude, Samson O.; Olatunji, Sunday J.; Oloyede, Solomon O.; Ogunlaja, Adeniyi S.; Bourne, Susan A.
ABSTRACT: Combustion of fuels containing organosulfur compounds has resulted in the emission of sulfur oxides (SO x ) into the atmosphere, therefore, causing serious environmental and health hazards. Herein, slightly distorted octahedral zig-zag 1D coordination polymer of copper(II) [Cu(4-mba)2 (H2 O)3 ] was synthesized by reacting copper sulfate pentahydrate with a carboxylate-containing ligand (H-4mba = 4-methoxybenzoic acid) and employed for sulfur compound uptake. The ligand coordinates to the copper(II) atom via two pairs of deprotonated ligating atoms (carboxylate oxygens) and two water molecules. Structural characterization also reveals that interplay of O–H···O, N–H···O, C-H···O and C–H···π interactions between lattice and coordinated water and ligands significantly contribute to the crystal packing leading to the formation and strengthening of three-dimensional supramolecular assembly. The complex, [Cu(4-mba)2 (H2 O)3 ], show potential for desulfurization of fuel with an observed adsorption capacity of 9.6 mg/g at 32°C for 6 h. DFT calculations further revealed a transfer of electron sulfur-containing compounds and the complex, [Cu(4-mba)2 (H2 O)3 ], thus leading to a stronger pi–pi interaction. GRAPHICAL ABSTRACT: